Guanine nucleotide binding protein involvement in early steps of phytochrome-regulated gene expression. - Romero, L C (1993)
The transmission process of light signals from plant photoreceptors to target cellular events is largely unknown. In the present work, we show that treatment of dark-adapted soybean cells (SB-P) with cholera toxin or pertussis toxin uncouples phytochrome-dependent gene expression. Addition of as little as 10 ng of toxin per ml is sufficient to activate expression of genes encoding the major chlorophyll a/b-binding protein (cab) in the dark. Significant levels of cab transcript accumulation are detected within 0.5 h after addition of the toxins and expression of these genes is desensitized to further light treatments. Treatment of SB-P cells with the calmodulin antagonist N-(6-aminohexyl)-5-chloro-1-naphtha-lenesulfonamide hydrochloride (W-7) prevents induction of the photoregulated gene by phytochrome or bacterial toxins. These results indicate the involvement of guanine nucleotide binding protein(s) in phytochrome-mediated cab gene activation. A likely site of action for this step is between the photoreceptor and a downstream W-7-sensitive effector.